A imigração haitiana em Cuiabá : perfil socioeconômico e a discriminação racial - Mathias, Orivaldo de Morais (2022)
This dissertation proposes a haitian population research in Cuiabá and the immigration consequences, analyzed by the socioeconomic status and the interviewers racial perceptions. In order to make this happen, interviews were conducted with haitian immigrants at Pastoral dos Migrantes de Cuiabá. This research aims to: a) understand the historical factors that brought the Haitians to Brazil and to Cuiabá; b) study the socioeconomic status of haitian immigrants in Cuiabá; c) question the interviewees about the institucional support of the Brazilian State for the haitian immigrants integration, such as: labour market integration, school education, and professional orientated education; d) identify whether racial prejudice and inequality related to the black brazilian population affect the haitian immigrants in Cuiabá. The dissertation discusses and criticizes the immigrant assimilation theories of The Chicago School; it relates the Brazil’s racial whiteness ideology to the present haitian migration-related issues; and it makes a dialogue about globalized economic contexts, in which the haitians are poor and peripheral immigrants. We characterized the research as quantitative and qualitative, although we emphasized words rather than quantification in data collection and analysis. Data collection took place through individual and recorded interviews with haitians in Cuiabá. They favored spontaneous responses in conversations, which formed a corpus of text to be used in writing the dissertation. Research data revealed widespread poverty, unemployment and underemployment among the haitian population, in addition to the racial and socioeconomic vulnerability of this immigrant population in Cuiabá. The theoretical approaches includes authors as Anthony Giddens (1991), Sílvio de Almeida (2019), Richard Alba; Victor Nee (2003), Thomas Skidmore (1976), Robert Park (2017) and Lilia Schwarcz (1993).